Preliminary Observation of the Changes in the Intestinal Flora of Patients With Graves’ Disease Before and After Methimazole Treatment - Yang, Mengxue; Zheng, Xiaodi; Wu, Yueyue; Zhang, Rui; Yang, Qian; Yu, Zhiyan; Liu, Jun; Zha, Bingbing; Gong, Qihai; Yang, Bo; Sun, Bowen; Zeng, Miao (Frontiers in Cellular and Infection Microbiology, 2022)
Immune dysfunction caused by environmental factors plays an important role in the development of Graves’ disease (GD), and environmental factors are closely related to the intestinal flora. Our previous study showed significant changes in the intestinal flora in GD patients compared with healthy volunteers. This study analyzed the relationships between changes in the intestinal flora, thyroid function and relevant thyroid antibodies in GD patients before and after methimazole treatment. The subjects were divided into the UGD group (18 newly diagnosed GD patients), the TGD group (10 GD patients with normal or approximately normal thyroid function after methimazole treatment) and the NC group (11 healthy volunteers). Their fresh stool samples were sent for 16S rRNA gene amplification and Illumina platform sequencing. The correlations of the relative abundance of Bifidobacterium with the levels of TRAb, TgAb and TPOAb in the NC group and the UGD group were analyzed. A total of 1,562,445 high-quality sequences were obtained. In the UGD group, the abundances of Bifidobacterium and Collinsella were higher than that in the NC group; Bacteroides abundance in the TGD group was higher than that in the NC group, while Prevotella and Dialister abundances were lower than that in the NC group; Prevotella and Collinsella abundances in the UGD group were higher than that in the TGD group. The predominant abundance distribution of Bifidobacteriaceae in the UGD group at the family level was superior to that in the NC group. The abundance of Bifidobacterium was positively correlated with the levels of TRAb, TgAb, and TPOAb. The biological diversity of the intestinal flora was reduced in GD patients. After methimazole treatment, the composition of the intestinal flora was significantly altered. The change in Bifidobacterium abundance was positively correlated with TRAb, TgAb and TPOAb, suggesting that it might be related to the immune mechanism of GD. The results of this study may deepen our understanding of the pathogenesis of GD and provide a new idea for the treatment of GD.